Back to the future the complete trilogy (Universal Studios, 2002)
Back to the Future: It's the mid-80's, and Marty McFly is your average 17-year-old slacker who happens to be friends with an inventor, Doc Brown. Doc's latest invention is a time machine, that ends up transporting Marty back to 1955 where he must bring his parents together so that he will exist when he gets back to his own time